THE PREVALENCE AND CLINICAL SIGNIFICANCE OF PERINUCLEAR ANTINEUTROPHIL CYTOPLASMIC ANTIBODY IN PATIENTS WITH INDETERMINATE COLITIS - Mahdi, Batool Mutar; Hasan, Riyadh Mohamad; Maki, Bassma; Hazim, Wafaa; Ghanim, Nahla; Al-Galabi, Leen Khalog (AL-Kindy College Medical Journal, 2011)
Background: Indeterminate colitis (IC), a termoriginated by pathologists to characterize confoundinghistopathlogic appearance of resected mucosa, hasbecome catch phrase for cases in which diagnosticcriteria at all levels elude classification as Crohn'sdisease (CD) or ulcerative colitis (UC).OBJECTIVES: evaluate the prevalence of pANCAexpression in the sera and its isotypes.Patients and methods: PATIENTS GROUPconsisted of 60 patients (40 males and 20 females)with indeterminate colitis and their age range was (19-84 years). CONTROL GROUP consisted of 30 (15males and 15 females) healthy volunteers and theirage range was (20- 66 years).Antineutrophil cytoplasmic ( pANCA and cANCA)testing was performed by an IIF technique on ethanolfixed human EOH granulocytes as substrate(EUROIMMUNE- Germany). Sigmoidoscope andcolonoscope examination were done for the patientsgroup and biopsies were taken from the patients forhistopathological examination.Results:Serological results of ANCA showed a significantincreased frequency of pANCA (63.3%) inindeterminate colitis patients as compared to controls(p=0.000). The highest percentage of this pANCAtiter was 1:10 (p=0.000) then 1:100 (p=0.008) andmost of them was IgG (53.3%) (p=0.000). Sensitivityof pANCA was 60%, specificity of pANCA was 40%,positive predictive value of pANCA was 61.1% andnegative predictive value of pANCA was 66.6%.cANCA did not demonstrated in both groups.Conclusions : pANCA was more prevalent inindeterminate colitis and could be used as a predictiveserological marker for the outcome of disease.